Nickel(II) N-Heterocyclic Carbene Complex for the Hydrogenation of 2-Acetylpyridine under Mild Conditions - Mitu Sharma; Amanda M. Perkins; Alison K. Duckworth; Emily J. Rouse; Bruno Donnadieu; Bhupendra Adhikari; Sean L. Stokes; Joseph P. Emerson (Inorganics, 2023)
Catalyst-mediated hydrogenation of ketones via hydride transfer can be directly used in the synthesis of alcohols which can exhibit great potential in the practical synthesis of pharmaceuticals. The application of Ni-NHC complexes in the hydrogenation of ketones is still limited. In a pursuit to study the effect of Ni-NHC-based complexes in the reactivity towards hydrogenation, we have studied the catalytic efficiency of a pendent-type nickel complex [Ni(NHC)2](PF6)2 constructed from a benzimidazole moiety. The hydrogenation of 2-acetylpyridine was studied with respect to catalyst loading, reaction temperature, reaction time, and solvent medium. The complex was broadly characterized by X-ray crystallography, ESI-MS, NMR, UV-Vis, and IR spectral studies.